Beyond Safety Training Embedding Safety in Professional Skills - Bieder, Corinne; Gilbert, Claude; Journé, Benoît; Laroche, Hervé; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is open access under a CC BY 4.0 license. This book investigates why, despite more and more resources devoted to safety training, expectations are not entirely met, particularly in the industrial sectors that have already achieved a high safety level. It not only reflects the most precious viewpoints of experts from different disciplines, different countries, with experiences in various industrial fields at the cutting edge of theories and practices in terms of safety, professionalization and their relationships. It also consolidates the positioning of the Foundation for an Industrial Safety Culture, highlighting what is currently considered at stake in terms of safety training, taking into account the system of constraints the different stakeholders are submitted to. It reports some success stories as well as elements which could explain the observed plateau in terms of outcome. It identifies some levers for evolution for at-risk industry and outlines a possibleresearch agenda to go further with experimental solutions.
Claude Gilbert -- Part I Critical assessments -- A practice-based approach to safety as an emergent competence, by Silvia Gherardi -- Line managers as work professionals in the era of workplace health professionalization, by Pascal Ughetto -- Captain Kirk, managers and the professionalization of safety, by Hervé Laroche -- A critique from Pierre-Arnaud Delattre, by Pierre-Arnaud Delattre -- Part II Is professionalism a safety issue or the other way round? -- Enhancing safety performance: non-technical skills and a modicum of chronic unease, by Rhona Flin -- Situated practice and safety as objects of management, by Petter Almklov -- Stories and standards: the impact of professional social practices on safety decision making, by Jan Hayes -- Doing what is right or doing what is safe, by Linda Bellamy -- Industrial perspective on the seminar: the viewpoint of a mining expert, by Jonathan Molyneux -- Dealing with the inherent contradictions of Professional development. Putting safety practices into discussion. A management approach, by Benoît Journé -- Part III Ways forward -- Can safety training contribute to enhancing safety?, by Corinne Bieder -- Training design oriented by works analysis, by Vincent Boccara -- Safety and behaviour change, by Paul Chadwick -- Power and love: recognizing the power of "those who make" for enhanced (safety) performances, through dedicated spaces for debate, by Nicolas Herchin -- Synthesis, by Caroline Kamaté, Hervé Laroche & François Daniellou.
Keywords: Security systems; Psychology, Industrial; Fire prevention; Buildings -- Protection; Economic sociology; Employee health promotion; Professional education; Vocational education; Security Science and Technology; Work and Organizational Psychology; Fire Science, Hazard Control, Building Safety; Economic Sociology; Employee Health and Wellbeing; Professional and Vocational Education